Neutrophil-to-lymphocyte ratio as a predictor of in-hospital complications and overall mortality in Takotsubo syndrome preceded by physical triggers - Hyo-Jeong Ahn; Jeehoon Kang; So-Ryoung Lee; Jin Joo Park; Hae-Young Lee; Dong-Ju Choi; Hyun-Jai Cho (BMC Cardiovascular Disorders, 2023)
Abstract Background Takotsubo syndrome (TTS) with physical triggers has worse short- and long-term clinical courses than those with emotional triggers. However, predictive factors associated with poor outcomes of TTS with physical triggers are unknown. Methods We included 231 patients identified as TTS preceded by physical triggers at two tertiary referral hospitals from 2010 to 2019. In-hospital complications (IHC)—a composite of malignant arrhythmia, need for mechanical circulatory support or mechanical ventilation, and in-hospital death—and overall mortality were retrospectively reviewed. The associations with clinical features were evaluated by multivariable logistic and Cox regression analyses. Results The mean age was 69.3 ± 11.6 years, and 85 (36.8%) were male. The in-hospital complications rate was 46.8%. During a median follow-up of 883 days, 96 (41.6%) had died, and overall mortality was 13.6% per patient-year. Higher neutrophil-to-lymphocyte ratio (NLR) was associated with a higher risk of IHC (area under the receiver operating characteristic curve = 0.73; positive and negative predictive value = 60.9% and 67.2% for NLR ≤ 12); odds ratio (OR) with 95% confidence interval (CI) was 1.03 (1.01–1.05), p = 0.010. Subsequently, higher NLR was also related to a greater risk of overall mortality; patients with high NLR (NLR > 12) exhibited poor long-term survival than those with low NLR (NLR ≤ 5): hazard ratio (95% CI), 3.70 (1.72–7.94) with p < 0.001. Conclusions A high NLR at initial presentation is associated with an increased risk of IHC and overall mortality in TTS preceded by physical triggers. Given that the treatment of TTS is mainly supportive, intensive monitoring with careful follow-up would be warranted in patients with high NLR.